Facile synthesis of iron oxide coupled and doped titania nanocomposites: tuning of physicochemical and photocatalytic properties. Issue 76 (1st August 2016) - Ganeshraja, Ayyakannu Sundaram; Rajkumar, Kanniah; Zhu, Kaixin; Li, Xuning; Thirumurugan, Subramani; Xu, Wei; Zhang, Jing; Yang, Minghui; Anbalagan, Krishnamoorthy; Wang, Junhu
Abstract : The iron oxide coupled and doped titania nanocomposites exhibited altered compositional, optical, electrical, magnetic and photocatalytic properties with respect to varying dosage of iron in the titania matrix. Abstract : A facile hydrothermal method was firstly employed to synthesize iron oxide coupled and doped titania nanocomposites using an aqueous solution of titanium nitrate. The present nanocomposites exhibit altered compositional, optical, electrical, magnetic and photocatalytic properties with respect to varying dosage of iron in the titania matrix. The architecture of characteristic iron oxide such as Fe2 O3 coupled with titania was confirmed by 57 Fe Mössbauer spectroscopy and X-ray absorption fine structure spectroscopic measurements. The enhanced photocatalytic activity was demonstrated by comparing with that of pure hematite, anatase TiO2, rutile TiO2 and P25 in the degradation of methylene blue under visible light ( λ > 480 nm) irradiation in an aqueous suspension. The strategy presented here gives a promising route towards the development of a metal oxide coupled and doped semiconductor material for applied photocatalysis and related applications.